Pendampingan Pemanfaatan Digital Branding dan Marketing untuk Pemasaran Hasil Panen Buah dan Bunga di Desa Bulukerto Kota Batu - Nisfulaila, Intan; Bisriyah, Maslihatul; Jayanti, Septia Dwi (JRCE (Journal of Research on Community Engagement), 2023)
The Covid-19 pandemic and the flash flood disaster in the end of 2021 affected the income of fruit and flower farmers in Bulukerto Village, Bumiaji District, Batu City. The focus of this community research is to assist groups of farmers in Bulukerto Village through workshops related to digital branding and marketing. The workshop activities include discussing together and sharing experience so that farmer groups get education and insight to be able to maintain and even increase their income using digital media. The workshop also conducted  through online discussion, monitoring, and evaluation activities by using WhatsApp group. The results of the series of activities are in the form of real steps by farmer groups to create unique and attractive brands of harvested products which are then marketed independently through platforms provided by social media.